THE INFLUENCE OF THE PRESENTATION OF FINANCIAL REPORTS, THE COMPETENCE OF THE APPARATUS AND THE GOVERNMENT'S INTERNAL CONTROL SYSTEM ON ACCOUNTABILITY VILLAGE FINANCIAL MANAGEMENT IN MUARA BATU SUB-DISTRICT NORTHERN ACEH DISTRICT - Nurul Mizna Sukma; Abdillah Arif Nasution; Amlys Syahputra Silalahi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to determine and analyze the effect of the presentation of financial reports, the competence of the apparatus and the government's internal control system on the accountability of village financial management in Muara Batu District, North Aceh Regency. This research is associative research and the type of data used is quantitative data. The population in this study were village officials in Muara Batu District, North Aceh Regency. The number of samples in this study amounted to 104 village officials in Muara Batu District, North Aceh Regency. The data analysis technique in this study used multiple linear regression. The results of this study indicate that the presentation of financial reports has a positive and significant effect on the accountability of village financial management in Muara Batu District, North Aceh Regency, apparatus competence has no effect on the accountability of village financial management in Muara Batu District, North Aceh Regency, and the government internal control system has a positive and significant effect on the accountability of village financial management in Muara Batu District, North Aceh Regency.